2011
DOI: 10.1186/1471-2288-11-76
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing cost-efficiency in mean exposure assessment - cost functions reconsidered

Abstract: BackgroundReliable exposure data is a vital concern in medical epidemiology and intervention studies. The present study addresses the needs of the medical researcher to spend monetary resources devoted to exposure assessment with an optimal cost-efficiency, i.e. obtain the best possible statistical performance at a specified budget. A few previous studies have suggested mathematical optimization procedures based on very simple cost models; this study extends the methodology to cover even non-linear cost scenar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 82 publications
0
19
0
Order By: Relevance
“…Most studies investigating this issue have considered only statistical efficiency, not measurement cost [11]. However, optimization based on both costs and statistical performance could yield a substantially different study design than what follows from optimizing only with respect to statistical performance [16,17,20]. For example, when within-worker variance is higher than between-worker variance and recruitment costs for engaging participants are high compared to costs for collecting more data from subjects already in the study, multiple measures on fewer workers may prove to be a more cost efficient sampling strategy than that suggested when only statistical performance is considered, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies investigating this issue have considered only statistical efficiency, not measurement cost [11]. However, optimization based on both costs and statistical performance could yield a substantially different study design than what follows from optimizing only with respect to statistical performance [16,17,20]. For example, when within-worker variance is higher than between-worker variance and recruitment costs for engaging participants are high compared to costs for collecting more data from subjects already in the study, multiple measures on fewer workers may prove to be a more cost efficient sampling strategy than that suggested when only statistical performance is considered, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been few comprehensive efforts to report the empirical costs of biomechanical exposure assessment, and these preliminary efforts did not include any information on the quality or statistical properties of exposure information delivered (35)(36)(37). Recently some studies have combined empirical costs and precision of occupational exposure estimates, although these have addressed cost efficiency in general terms (20), or have focused on a narrow assessment of cost and compared sampling or analysis strategies just within a single method [in casu, observation; (19,21)]. …”
mentioning
confidence: 99%
“…Although these articles have furthered inquiry into efficient exposure assessment from a statistical point of view, they have been criticized for rarely acknowledging the actual costs of exposure assessment. Thus, a 2010 systematic review of literature focusing on cost-efficient collection of exposure data (18) found only nine studies dealing with the trade-off between statistical performance and monetary resources invested in obtaining that performance, even if some studies have appeared after 2010 (19)(20)(21). Only some of the publications identified in the 2010 review dealt specifically with occupational or environmental exposures (7,(22)(23)(24)(25)(26); only two of these included empirical data to illustrate cost and efficiency (24,26), and none were devoted to assessment of biomechanical exposure.…”
mentioning
confidence: 99%
“…Furthermore, different stages in a data collection process may entail different costs, and so the most efficient strategy in a statistical sense may not necessarily be the most cost-efficient [12]. Very little research has been devoted to investigating trade-offs between cost and statistical efficiency in data collection [17], and no studies have so far focused on the generic issue in video-based observation of whether resources -as constrained by a limited budget -should be allocated to collecting "many" video recordings and have them observed by "few" observers, or to a more meticulous observation of fewer video recordings.…”
Section: Introductionmentioning
confidence: 99%